Program Pesantren Ramadhan Sebagai Upaya Pencegahan Kekerasan di SMP Negeri 2 Pakem Bondowoso - Heridianto, Heridianto; Ikromah, Ikromah (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2025)
The Ramadan Islamic Boarding School Program is an annual program held at SMP Negeri 2 Pakem Bondowoso as a means to deepen basic Islamic knowledge for students. This article aims to explore the results and understanding of the Pesrom Program in improving students' understanding of how to prevent violence in schools. The research method used is a method to introduce sensitivity knowledge and skills to students that allows them to jump directly into a diverse cultural group. This method is divided into five stages, namely the preparation stage, the action stage, the reflection stage, the evaluation stage, and the celebration stage. The results of the study show that (1). Religious, including increasing students' understanding of religious teachings, students' consistency in carrying out compulsory worship. And the active participation of students in religious activities. (2). Social, including the development of students' social skills, building a sense of togetherness and solidarity, establishing a more harmonious relationship between students, teachers and school staff. (3). Education, including the ability of students to apply Islamic values in daily life.